2019
DOI: 10.1007/s42452-019-1855-8
|View full text |Cite
|
Sign up to set email alerts
|

New Brazilian pineapple leaf fibers for textile application: cottonization and dyeing performance

Abstract: This work evaluates the dyeing performance associated with a cottonization and bleaching pretreatment of pineapple leaf fibers from two different species from Brazil: curaua (A. lucidus syn. A. erectifolius) and red pineapple (A. bracteatus (Lindl.) Schult. & Schult.f ), aiming its application in textile materials for garments. Treated and untreated fibers were compared for their morphological, chemical, physical and color properties. The fibers underwent changes in their chemical and physical structural chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 26 publications
(24 reference statements)
0
6
0
Order By: Relevance
“…Similar results have been observed for Typha or pineapple leaf fibers. 26,38 However, for bamboo treated fibers, we obtain linear density values ​​slightly low 39 which is justified by the effect of the treatment on bamboo treated fibers.…”
Section: Resultsmentioning
confidence: 69%
See 1 more Smart Citation
“…Similar results have been observed for Typha or pineapple leaf fibers. 26,38 However, for bamboo treated fibers, we obtain linear density values ​​slightly low 39 which is justified by the effect of the treatment on bamboo treated fibers.…”
Section: Resultsmentioning
confidence: 69%
“…24 The linear density was measured in each of the sampling 22,23 zones and was calculated using equation (1) which was applied for Mesocarp oil palm and pineapple leaves fibers. 25,26…”
Section: Linear Densitymentioning
confidence: 99%
“…43 The pick at around 2915 cm À1 specifies the C-H stretching of cellulose and saturated alkane of wax. 5,44 Another study shows that the sharp band at 2915 cm À1 is caused by the C-H stretching of methyl and methylene groups in cellulose and hemicellulose. 45 With an increase in carding passages, it was found that the peaks observed in the range of 3100 to 3800 cm À1 , caused by the OH stretching vibration of intra-and intermolecular H-bonding in cellulose, hemicellulose, and lignin molecules, decreased noticeably due to the removal of extraneous substances from PALF.…”
Section: Ftir Analysis Of Palfmentioning
confidence: 99%
“…Throughout its history, the textile industry has been a major contributor to large-scale resource consumption. This is not only because textiles are among the most vital products, but also to the wide range of applications available, such as technical textiles (de Queiroz et al , 2020). Along with the increase of application types, increased demographic and socio – economic expansion results in an increasing discrepancy between fiber availability and demand, a concept is known as the fiber gap (Scheffer, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Natural fibers have become much more apparent as an alternate to synthetic fibers, not just for textiles but also for a diverse variety of other applications (de Queiroz et al , 2020). Natural fibers are biodegradable, as contrast to man made fibers, which are frequently employed in the textile industry (Kozlowski and Mackiewicz-Talarczyk, 2020).…”
Section: Introductionmentioning
confidence: 99%